Conflict between tax legislation and bankruptcy legislation in the company reorganization procedure: Destabilization of the unity of the legal order - Drobnjak Bojana (Zbornik Radova Pravnog Fakulteta u Nišu)
This article discusses the need to resolve the conflict between bankruptcy legislation and tax legislation regulating the subject matter of company reorganization procedure. The response rests on addressing several crucial questions: Is the presence of two directly conflicting legislations the foundation for a sound reorganization procedure? Is it possible to apply a lex specialis "derogated" by a general norm of tax legislation, which entails a constant danger of applying the compulsory (forced) collection mechanism? The write-off and successive payment of claims, as one of the basic reorganization tools, is threatened by the amendments to tax legislation. Failure to resolve the points of dispute in these two legislative areas leads to legal uncertainty. On the one hand, it enables the implementation of a wide range of measures provided in bankruptcy legislation. On the other hand, it provides leeway for the questionable use of coercive apparatus by the tax administration, which can lead to irreparable damage to the company in reorganization, founders and creditors, but it may also be harmful for the tax administration itself. To ensure the most favorable settlement of creditors after the initiation of bankruptcy proceedings, it is first essential to identify the objectives of conflicting legal norms, then to address the existing contradictions between these objectives, and finally to redefine them by resolving the conflicts of legal norms in accordance with the social circumstances in which these norms are applied.